The Development of The Cartoon-Assisted Practicum Guideline To Enhance Students’ Science Process Skills in Physics Learning - Fianti Fianti; Eka Nurhidayah; Bambang Subali; Putut Marwoto; Husna Arifah (Jurnal Pendidikan Fisika Indonesia, 2026)
A practicum guideline is a learning medium designed to support laboratory activities. This study aimed to develop a cartoon-assisted practicum guideline and to evaluate its feasibility, characteristics, and effectiveness in enhancing students’ science process skills (SPS). The research used a Research and Development (R&D) approach with a modified 4D model (define-design-development, without dissemination). The developed practicum guideline focuses on a thin lens laboratory activity for high school students and is intended to support the teaching and learning of optics. The inclusion of cartoon characters was specifically designed to increase students’ motivation, provide visual representations of key concepts, clarify content and procedural steps, guide and maintain students’ focus, and facilitate overall comprehension. The feasibility test result showed that the developed product was very feasible, with overall feasibility indices of 83.15% and 84.84% as evaluated by practitioners and experts, respectively. The assessment covered four aspects: (i) content, (ii) presentation, (iii) language, and (iv) graphics. The product was classified as a good practicum guideline, as it applied the "visual principle", was coherently arranged to guide students through the practicum activity, and developed their SPS through appropriate supplementary features. Students’ responses to the implementation of the cartoon-assisted practicum guideline were in good categories, as they reported feeling happy, enthusiastic, and interested in conducting laboratory activities. Therefore, it can be concluded that the cartoon-assisted practicum guideline was successfully developed and was partially effective in improving students’ SPS.